Banking productivity analysis in Indonesia: Empirical evidence using Malmquist Productivity Index based DEA and an Error Correction Model approach - Dini, Dini Rahmayanti; Ariyani, Diyah; Rismaya , Anisa Dewi (Nur Science Institute, 2023)
The level of productivity can be used as a benchmark for assessing the performance of a bank so that we can find out how efficient a bank's performance is or how banking productivity is so that we can still get maximum and efficient performance amidst the many choices of customers in choosing bank. This research examines how banking productivity has changed in Indonesia, using banking report data in Indonesia for the 2017-2022 period. Data Envelopment Analysis (DEA) linear programming model, which is used based on the Malmquist Index to measure changes in Total Factor Productivity (TFP). Regression model to describe what variables influence changes in banking productivity in Indonesia. With the Error Correction Model, the Loan-to-Deposit Ratio (LDR) and Return on Equity (ROE) have a significant effect on productivity in the long term. The pandemic crisis does not affect productivity. Meanwhile, in the short term, Net Interest Margin has a significant effect on banking productivity in Indonesia.